Facial Gold Reinforcement: 28 Years of Experience in the Use of Gold Threads - Alexey E. Avdeev; Valentin I. Sharobaro; Arslan A. Penaev; Anastasia S. Borisenko; Elena V. Mitish; Anna S. Bairamova (Cosmetics)
Introduction: Gold threads became widely used in esthetic surgery in the early 1990s. Produced in Spain, these threads consisted of a gold thread (5/0) with a diameter of 0.1 mm, composed of 99.99% pure gold, which was combined with a polyglycolic thread. Since then, discussions about their effectiveness have continued, which is the focus of our study. Patients and Methods: Gold thread implantation was performed on 11,062 patients in four clinics in Moscow over the course of 28 years. This study used a comparative analysis of photo collages created for the visual representation of data and changes before and after the procedure, as well as patient satisfaction assessments using the Patient Satisfaction Scale (PSS). We examined the results of 492 patients who underwent gold thread implantation in the face between 1996 and 2024. Of these patients, 86% were women aged 30 to 60 years, 11% were women aged 20 to 30 years, and 3% were men aged 25 to 60 years. Results: One year after thread implantation, the PSS assessment showed a 91% success rate with minimal complications. Patient satisfaction was high, with an average score of 4.8 out of 5 after one month, 4.7 after six months, and 4.6 after one-year post-procedure. Discussion: Gold thread implantation is a minimally invasive procedure that has demonstrated a high level of safety, making it an effective option for facial rejuvenation. Histological studies have shown that gold threads stimulate the production of collagen and elastin and activate angiogenesis, thereby improving skin nourishment and hydration, as well as enhancing the skin tone, elasticity, and turgor. To improve the qualitative characteristics of the skin, it is necessary to work in the subcutaneous layer. Conclusions: Gold thread implantation strengthens the connective tissue framework at the implantation site, thus improving skin nourishment and hydration. Gold threads provide a long-term rejuvenating effect, slowing the ptosis of the soft tissue of the face and neck. Gold thread implantation does not interfere with tissue dissection during surgical interventions or the performance of any cosmetic procedures, including hardware-based treatments.